Joining the DOTS: A collaborative approach to online teacher training - Stickler, Ursula (Array, 2010)
Developing Online Teaching Skills (DOTS) is one of 20 “Empowering language professionals” projects currently funded by the Council of Europe's European Centre for Modern Languages (ECML). Its principal aim is to develop an online platform for delivering teacher training at a distance. Once completed, this collaborative platform will contain a range of modular activities for self-training via a selection of interactive CMC tools. This paper describes the participative process involved in developing this platform and in creating bite-size introductory activities to online tools for language teaching based on the input of online learning experts and users from 25 European countries.